Edukasi Keterampilan Esensial di Era AI untuk Generasi Muda Komunitas Senyum Anak Bandung - Kristinawati, Didin (Jurnal SOLMA, 2024)
Background: The importance of mastering essential skills in the era of artificial intelligence (AI) is becoming increasingly urgent with the changing job landscape influenced by automation and digital technology. The purpose of organizing education on essential skills in the AI era is to enhance understanding of AI phenomena and their impact on the job market, including both jobs at risk and emerging new jobs. Method: This community service activity was conducted for members of the Senyum Anak Bandung Community on June 8, 2024, with 35 participants. The event was held at Tikita Coffee Bandung, located at Jalan Brigadir Jendral Katamso number 19B, Bandung City. The program started at 1:00 PM and concluded at 6:00 PM. The methodology of this activity was divided into three stages: preparation, implementation, and evaluation. Results: The material presented included the definition of AI, examples of practical applications, and the implications of AI on the job market, illustrating significant changes in skill demands in the digital era. In addition to technical skills, this education emphasized soft skills such as problem-solving, communication, resilience, and persistence. These skills are essential not only for solving complex problems and communicating effectively but also for developing mental resilience and the ability to endure life's challenges. Conclusion: Moving forward, it is recommended to continually integrate formal education with lifelong learning and the development of cognitive and social skills to ensure that young generations are prepared to adapt to rapid technological changes.